2017
DOI: 10.3389/fnins.2017.00197
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Auditory Feedback of Eye Movements: An Exploratory Study toward Improving Oculomotor Control

Abstract: As eye movements are mostly automatic and overtly generated to attain visual goals, individuals have a poor metacognitive knowledge of their own eye movements. We present an exploratory study on the effects of real-time continuous auditory feedback generated by eye movements. We considered both a tracking task and a production task where smooth pursuit eye movements (SPEM) can be endogenously generated. In particular, we used a visual paradigm which enables to generate and control SPEM in the absence of a movi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The success rate contributed to the monetary reward paid out at the end of the session. Such real-time sonification of smooth pursuit may successfully improve performance in several tasks (Boyer, Portron, Bevilacqua, & Lorenceau, 2017), but requires extensive practice (several hours).…”
Section: Predictive Pursuit Is Finely Tuned To Target Propertiesmentioning
confidence: 99%
“…The success rate contributed to the monetary reward paid out at the end of the session. Such real-time sonification of smooth pursuit may successfully improve performance in several tasks (Boyer, Portron, Bevilacqua, & Lorenceau, 2017), but requires extensive practice (several hours).…”
Section: Predictive Pursuit Is Finely Tuned To Target Propertiesmentioning
confidence: 99%
“…Therefore, it may be effective to provide constant real-time feedback on eye-movements according to individuals' response in attention training. The results of previous studies highlighted that real-time constant feedback on eye-movements could modify the oculomotor behavior and reinforce intrinsic oculomotor perception (30). In addition, in the studies that used constant eye-gaze contingent feedback, training was found to lead to an efficient implementation of attentional control (31).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, care should be taken when providing feedback to the user, as visually prominent feedback mechanisms could have unintended consequences of shifting the users gaze unless the feedback is provided on the selected object itself. Using non-visual feedback, such as auditory feedback, Boyer et al (2017) would be an alternative approach. Examples of visual feedback for eye gaze-based interaction include: highlighting the selected object (Blattgerste et al 2018); displaying an outline around the selected object (Sidenmark et al 2020), and showing confirmation flags around the selected object (Mohan et al 2018).…”
Section: Selection and Manipulationmentioning
confidence: 99%